Chemical pesticide tends lower appreciating alternatives of pest of control: Bangladesh perspective - Abul Khayer Mian (Open Journal of Plant Science - Peertechz Publications, 2021)
Pesticide is commonly used for growing more food successfully to feed the increasing population of Bangladesh. It is a great challenge to provide food to people coping with the demand of nation. Consequently, high inputs like fertilizer, irrigation, pesticides were adopted to enhance crop productivity. Now, it is well known that pesticide has many harmful effects. Extensive expose of pesticides resulted in contamination of air, soil, water and food [1], interring into the food chain caused human health hazard and diseases) [2].